Acoustic Emissions in Geotechnical Engineering Practice 1981
DOI: 10.1520/stp28342s
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Acoustic Emission Techniques to Rock and Rock Structures: A State-of-the-Art Review

Abstract: This paper presents a state-of-the-art review of the subject of acoustic emission as it pertains to the area of rock mechanics, and includes references to some 150 recent papers. Although a limited discussion of laboratory oriented studies are included, the major thrust of the paper is to field applications in geotechnical engineering. The paper first discusses the general concepts involved in the acoustic emission technique and briefly reviews the early history of the subject. This is followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
5

Year Published

1988
1988
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 23 publications
0
16
0
5
Order By: Relevance
“…Diederichs suggested that plotting the Poisson's ratio Eberhardt et al (1998) have used several techniques to detect crack initiation for Lac du Bonnet granite such as stress-strain data, the moving point regression technique and acoustic emission (AE). Acoustic emission is a lowenergy seismic event which is generated by inelastic deformation such as grain dislocation or crack initiation (Hardy 1981). These three techniques can be used together to find a more reliable result ( Fig.…”
Section: Lateral Strain Methodsmentioning
confidence: 99%
“…Diederichs suggested that plotting the Poisson's ratio Eberhardt et al (1998) have used several techniques to detect crack initiation for Lac du Bonnet granite such as stress-strain data, the moving point regression technique and acoustic emission (AE). Acoustic emission is a lowenergy seismic event which is generated by inelastic deformation such as grain dislocation or crack initiation (Hardy 1981). These three techniques can be used together to find a more reliable result ( Fig.…”
Section: Lateral Strain Methodsmentioning
confidence: 99%
“…El Moundni et al, 2000;Gori et al, 2000;Hardy 1972Hardy , 1981Hardy , 2003Knill et al, 1968;Koerner et al, 1981;Lockner and Byerlee 1995;Lord and Koerner 1979;McCabe 1980;Mogi, 1962;Pollock 1977;Rogers 2000;Scholz 1968;Surgeon et al, 2000;Wood et al, 1984;Yuyama 1986).…”
Section: Appendix Amentioning
confidence: 99%
“…Accompanying these processes, an elastic stress wave is generated, which travels from the point of origin within the rocks to a boundary, where it is observed as an AE signal. Many studies have been devoted to the application of AE monitoring techniques in rock engineering and it is generally understood that AE signals in rocks that can be detected by AE transducers have a frequency range between 10 4 and 10 6 Hz [5,14].…”
Section: Introductionmentioning
confidence: 99%